Quantification of Zonula Occludens-1 mRNA expression in cultu-red bovine retinal endothelial cells, using SYBR green real-time PCR - Ismail, I.S.; Muniandy, S.; Koon, C.Y.; Bee, J.C.; Rayappan, A.V.; Kum, T.W.; Qvist, R. (Biomedical Research Press, 2008)
A simple and rapid real-time reverse transcription-PCR (RT-PCR) technique using SYBR green fluorescence was developed to quantify Zonula Occludens-1 (ZO-1) mRNA expression in histamine-treated cultured bovine retinal microvessel endothelial cells. There was no difference between the quantity of ZO-1 mRNA expression in histamine-treated (10-7M to 10-9 M) and untreated bovine retinal endothelial cells at high magnesium levels. Immunohisto-chemistry staining and western blot assay unequivocally demonstrated the approximately similar levels of ZO-1 protein in both histamine-treated and non-treated endothelial cells at high magnesium concentrations.